Peran Kepemimpinan dalam Peningkatan Kinerja Pegawai di Bagian Staf Administrasi Kepala Staf Angkatan Udara (SMIN KASAU) Markas Besar TNI Angkatan Udara - Dwi Ratnasari (Madani Connection, 2025)
This research aims to analyze the role of leadership in improving employee performance in the Administrative Staff section of the Air Force Chief of Staff (SMIN KASAU) of the Indonesian National Army Headquarters, as well as identifying factors that support and hinder the role of leadership in improving employee performance. This research uses a qualitative approach with interview techniques, observation and focus group discussions to explore deeper understanding. The findings of this research indicate that the leadership model applied in the Administrative Staff of the Chief of Staff of the Indonesian National Army Air Force implements all leadership roles according to Path Goal theory, namely leaders as directors, leaders as supporters, leaders as participants and leaders who are achievement oriented. Factors that support the implementation of good leadership in the Administrative Staff of the Chief of Staff of the Indonesian National Army Air Force include good cooperation, quality of performance, timeliness, accuracy in giving orders and the availability of adequate facilities and infrastructure.